Delivering Education to the Underserved through a Public-Private Partnership Program in Pakistan - Barrera-Osorio, Felipe; Blakeslee, David S.; Hoover, Matthew; Linden, Leigh L.; Raju, Dhushyanth; Ryan, Stephen P. (World Bank, Washington, DC, 2017)
This study experimentally evaluates the short-term impacts of public per-student subsidies to partnering local entrepreneurs to establish and operate tuition-free, coeducational, private primary schools in educationally underserved villages in Sindh province, Pakistan. Two subsidy structures were tested, one in which the subsidy amount did not differ by student gender, and the other in which the subsidy amount was higher for female students. The program administrator introduced the latter structure with the aim of correcting for the gender disparity in school enrollment in the general program setting. The program increased school enrollment by 30 percentage points in treated villages, for boys and girls. It increased test scores by 0.63 standard deviations in treated villages. The gender-differentiated subsidy structure did not have larger impacts on girls' enrollment or test scores than the gender-uniform one. Program schools proved more effective in raising test scores than government schools located near the villages, with program-school students scoring 0.16 standard deviations higher, despite coming from more socioeconomically disadvantaged backgrounds. Estimations of the demand for schooling and education production suggest nearly efficient choices on school inputs by the program administrator and partnering entrepreneurs.